Connectedness Among Chilean Adolescents: Factor Analysis of the Hemingway Measure of Adolescent Connectedness - McWhirter,Benedict T (Pontificia Universidad Católica de Chile, 2011)
The construct of connectedness was investigated among 390 Chilean adolescents using the Hemingway Measure of Adolescent Connectedness (Hemingway; Karcher, 2003). Participants were 7th-12th graders at an urban Santiago Catholic school. Results of a principal-axis exploratory factor analysis revealed an 11 factor structure that accounts for 61.92% of total explained variance of adolescent connectedness measured by the Hemingway, similar to results found in the adolescent samples in the United States. Two additional Hemingway subscales (connectedness to siblings and to boyfriend/girlfriend) are also described. Correlations between domains of connectedness and additional data obtained from these adolescents, their parents, and their teachers support the construct validity of the measure in this Chilean sample. Connectedness is an important protective factor among adolescents across many national contexts and the Hemingway is a promising measure for use with Chilean adolescents.